Microbiological monitoring in the first kidney transplant - Athukorale, S.D.; Sheriff, M.H.R. (My University, 1986)
Microblological monitoring in an immune compromised most like a kidney transplant patient is a vital component of the post transplant care. Monitoring starts prior to surgery with swabs being taken from the mouth, ears, nose, skin and penis of the recipient. Urine cultures were done on both the recipient and the donor just prior to surgery. Swabs were repeatedly taken once in 3-4 days from the sites mentioned and the ready-vac drain site from the immune supressed recipient in the first 10 days. Urine cultures were done on the recipient on days 1,2,4,6,7,8, 10, 13 during the 1st two weeks. All drains, I. V. lines and catheters removed were cultured. Swabs from the nose, ready-vas drain site and nose grew significant bacterial growths and appropriate steps were taken to overcome the infection depending on the antibiotic sensitivity patterns. The swabs from the surgical incision and blood culture remained sterile throughout. Urine cultures were done twice a week in the 2nd to the 4th week, and weekly after that till repeated cultures were sterile and as the patient continued to be on reducing doses of immunesupression. There were several significant positive cultures during this period and antibiotics as 'well as urinary pH alterations were, used in order to overcome the threat of infection. The most important concept in post transplant microbiological monitoring is to pick up bacterial clinical stage and treat and least nephrotoxic antibiotics very aggressively.